PROTOTYPE APLIKASI PENGOLAHAN DATA WAREHOUSE PADA PT TELKOM AKSES: Prototype;Application;Data Warehouse. - Adhiatma, Novri; Ikhsan, Muhammad; -, Tamrinsyah (JURNAL AKADEMIKA, 2021)
Data warehouse processing is a storage medium in a company that collects data from various systems and can be used for various purposes such as reporting and analysis. In PT Telkom, access to warehouse data processing is still done in a conventional way, namely by recording data to the main book. Because it still uses the conventional method, in the data collection process there are often some shortcomings of errors that occur in the accumulation of data on the archive table, loss and damage to physical data, the data recording process cannot be on time, the data recording is not timely because I have to. In this research, it aims to help PT Telkom Access in designing a data warehouse application prototype using web-based technology. With the use of a website, the data warehouse can be processed and analyzed quickly and is not limited to physical space.